2021
DOI: 10.1111/jipb.13058
|View full text |Cite
|
Sign up to set email alerts
|

Arabidopsis U‐box E3 ubiquitin ligase PUB11 negatively regulates drought tolerance by degrading the receptor‐like protein kinases LRR1 and KIN7

Abstract: Both plant receptor‐like protein kinases (RLKs) and ubiquitin‐mediated proteolysis play crucial roles in plant responses to drought stress. However, the mechanism by which E3 ubiquitin ligases modulate RLKs is poorly understood. In this study, we showed that Arabidopsis PLANT U‐BOX PROTEIN 11 (PUB11), an E3 ubiquitin ligase, negatively regulates abscisic acid (ABA)‐mediated drought responses. PUB11 interacts with and ubiquitinates two receptor‐like protein kinases, LEUCINE RICH REPEAT PROTEIN 1 (LRR1) and KINA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
44
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(45 citation statements)
references
References 81 publications
1
44
0
Order By: Relevance
“…Many members of PLANT U BOX (PUB) E3 ligases have been shown to be involved in drought stress tolerance regulation ( Table 1 ). In Arabidopsis, PUB11 negatively regulates drought stress response by targeting LEUCINE RICH REPEAT PROTEIN 1 (LRR1) and KINASE 7 (KIN7) for degradation via the 26S proteasome [ 67 ]. Both LRR1 and KIN7 are needed to promote stomatal closure during water stress conditions [ 172 , 173 ].…”
Section: Drought Stressmentioning
confidence: 99%
See 1 more Smart Citation
“…Many members of PLANT U BOX (PUB) E3 ligases have been shown to be involved in drought stress tolerance regulation ( Table 1 ). In Arabidopsis, PUB11 negatively regulates drought stress response by targeting LEUCINE RICH REPEAT PROTEIN 1 (LRR1) and KINASE 7 (KIN7) for degradation via the 26S proteasome [ 67 ]. Both LRR1 and KIN7 are needed to promote stomatal closure during water stress conditions [ 172 , 173 ].…”
Section: Drought Stressmentioning
confidence: 99%
“…These E3 ligases also function as monomeric E3s and encompass less than 100 members in plants [ 54 , 55 , 56 , 57 ]. They function widely in abiotic and biotic stress responses, but have also been described, for example, in apical meristem maintenance or phytohormone signaling [ 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 ].…”
Section: Introductionmentioning
confidence: 99%
“…In Arabidopsis, it was reported that two receptor-like kinases, LRR1, and KIN7 are targeted by PLANT U-BOX PROTEIN 11 (PUB11), an E3 ubiquitin ligase, and lead to their degradation during drought stress. This is regulated through abscisic acid ( Chen et al, 2021c ). The receptor-like protein kinase HAIKU2 is a type of leucine-rich receptor-like protein kinase (LRR-RLK).…”
Section: Resultsmentioning
confidence: 99%
“…Protein degradation is also a way for crop plants to adapt to drought stress. For example, the E3 ubiquitin ligase gene is involved in protein degradation during drought stress, which includes several subfamilies: (1) RING finger gene family members OsDSG1 [ 109 ], OsRDCP1 [ 110 ], OsSDIR1 [ 111 ], StRFP2 [ 112 ], and TaSDIR1 [ 113 ]; (2) U-box gene family member PUB11 [ 114 ]; (3) F-box gene family members SAGL1 and ECERIFERUM3 [ 115 ]; and (4) CUL4-DDB1 gene family member HOS15 [ 116 ].…”
Section: Genes Related To Drought Tolerancementioning
confidence: 99%
“…[109], OsRDCP1[110], OsSDIR1[111], StRFP2[112], and TaSDIR1[113]; (2) U-box gene family member PUB11[114]; (3) F-box gene family members SAGL1 and ECERIFERUM3[115]; and (4) CUL4-DDB1 gene family member HOS15[116].…”
mentioning
confidence: 99%